ANALISIS RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN TUBAN TAHUN 2021-2026 DALAM PERSPEKTIF EVIDENCE BASED POLICY: - Iswanto, Denny (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
The application of Evidence-Based in policy formulation and development planning in Indonesia is still new and important to be implemented to reduce the dominance of political interests and prioritize public interests in the policy-making process. The implementation of evidence-based policy is an urgency in the regional development planning agenda, especially in Tuban Regency. This study aims to understand the evidence-based policies that have been implemented in the RPJMD of Tuban Regency for 2021-2026. This type of research is descriptive qualitative research with a secondary data analysis method. The results showed that this planning document has implemented evidence-based planning development in Tuban Regency. However, the quality of evidence still needs to be improved, especially at the top level, which are the use of research and scientific articles to be considered in determining regional development policies. Evidence-based development can improve the accuracy of development programs and increase the effectiveness of policy implementation in implementing public services. With the awareness and willingness to implement evidence-based policy, stakeholders can use data and information as evidence that is more focused, concrete, grounded, and sensitive to society issues.